Democratic Stability in Mitigating the Impact of Corruption on Economic Growth in Nigeria - Isiwu George Duhu (European Scientific Journal, ESJ, 2019)
Corruption and its practices in Nigeria have become systemic in both public and private sectors. Following the consolidation of democracy in the country since 1999 to date, there is a problem as to whether democratic stability has helped in mitigating the impact of corruption on economic growth. The main objective of this study is to identify whether democratic stability helps in mitigating the impact of corruption on Economic growth in Nigeria. Annual time series data on real GDP growth rate, corruption perception index (proxy for corruption), life expectancy at birth, population growth rate and government expenditure were the variables used for the study, covering the period 1996-2017. Dummy variable was also used as a proxy for democracy. To analyse the data, Autoregressive Distributed lag (ARDL) model was adopted. The empirical results show that corruption has negative impact on economic growth, implying that increase in corruption decreases economic growth; and that democratic stability helps in mitigating the impact of corruption on economic growth in Nigeria during the period covered by the study. The study, therefore, recommends that the government should enforce the democratic principles such asthe rule of law, government’sresponsiveness to public opinion, freedom of speech, freedom of religion and most importantly, political participation by the citizens. Such democratic principles, when enforced, will provide more stable environment for investments and hence promote growth. The various anti-corruption agencies like the EFCC and ICPC should also, without fear or favour, bring to book all corrupt politicians and bureaucrats in our public service.